Prealgebra (7th Edition)

Published by Pearson
ISBN 10: 0321955048
ISBN 13: 978-0-32195-504-3

Chapter 4 - Review - Page 322: 98



Work Step by Step

$-2\frac{1}{4}\times1\frac{3}{4}$ $=-(2\frac{1}{4}\times1\frac{3}{4})$ $=-(\frac{9}{4}\times\frac{7}{4})$ $=-\frac{63}{16}$ $=-3\frac{15}{16}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.